1970
DOI: 10.1161/01.cir.42.5.903
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Electrocardiographic Concept Useful in the Diagnosis of Cor Pulmonale

Abstract: ysema Bronchitis Asthmatic bronchitis demonstrate electrocardiographically in many cases. A relatively small number of patients in this survey (24 of 200) satisfied criteria previously published for ECG diagnosis of RVH, 1-5 and indeed these characteristics were not present in 72% of our patients with cor pulmonale. The published criteria,1-5 however, were secured largely from patients with congenital heart disease, a very different population from that of cor pulmonale. We have learned that pulmonary hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
10

Year Published

1976
1976
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 22 publications
1
10
0
10
Order By: Relevance
“…Thus, ECG stability does not exclude hemodynamic aggravation, especially in cases of PAH, but a worsening ECG picture, as defined in this work, almost always indicates worsening of PAH. These results are in general agreement with a previous study [18] limited to cases of CPC, and they illustrate the diag nostic value of ECG follow-up which has been emphasized in recent years [6].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, ECG stability does not exclude hemodynamic aggravation, especially in cases of PAH, but a worsening ECG picture, as defined in this work, almost always indicates worsening of PAH. These results are in general agreement with a previous study [18] limited to cases of CPC, and they illustrate the diag nostic value of ECG follow-up which has been emphasized in recent years [6].…”
Section: Discussionsupporting
confidence: 92%
“…Electrocardiographic changes have been previously reported in COPD patients with cor pulmonale diagnosed clinically or during an autopsy (16, 17, 27-29). The ECG findings suggestive of right ventricular hypertrophy occur late in the course of the disease (16) and are difficult to differentiate from the rotational changes or electrical insulating effects caused by the hyperinflated lungs (17, 30).…”
Section: Discussionmentioning
confidence: 90%
“…However, the ECG findings may be late (16) and not always reliable for this diagnosis (17) due to their poor sensitivity (18-21). ECG abnormalities are more commonly seen in COPD patients than age-matched controls and their prevalence increases with severity of pulmonary obstruction (22).…”
Section: Introductionmentioning
confidence: 99%
“…Kilcoyne et al [20] reported that the sensitivity of Sokolow and Lyon [21] was 28% in the patients with cor pulmonale whose ECG showed the pattern of right ven tricular hypertrophy. Walker et al [22] reported that the sensitivity of the ECG criteria proposed by Sokolow and Lyon [21] was 22.7% and that those of Myers et al [23] was 13.6% in autopsy-proven cases of isolated right ven tricular hypertrophy.…”
Section: Diagnosis Of Rvo From the Ecg And Mcgmentioning
confidence: 99%